High contribution of vehicular exhaust and coal combustion to PM2.5-bound Pb pollution in an industrial city in North China: An insight from isotope. (1st February 2023) - Chen, Hao; Yan, Yulong; Hu, Dongmei; Peng, Lin; Wang, Cheng
Abstract: Although industrial emissions are the major pollution source of PM2.5 -bound Pb, which affects air quality in cities, their influence has gradually decreased with the enhancement of industrial control in recent years. Thus, at present, the source of PM2.5 -bound Pb is unclear, especially in an industrial city in North China. In this study, by incorporating the stable Pb isotopic compositions into a Bayesian isotope mixing model (MixSIAR), source apportionment of PM2.5 -bound Pb was conducted during autumn and winter in 2017, and summer in 2018 in Changzhi. The daily average concentrations of PM2.5 and PM2.5 -bound Pb during the study period were lower than the second-grade limit value of China (75 μg m −3 ) and the Chinese National Ambient Air Quality Standard (1 μg m −3 ), respectively. The pollution sources of PM2.5 -bound Pb were fully distinguishable using Pb isotopes. In Changzhi, the 206 Pb/ 207 Pb ratio in soil (average: 1.0891) and exhaust dust from gasoline (average: 1.0832) and diesel (average: 1.0814) showed low levels of Pb isotope signature in Changzhi, whereas the rest of the source exhibited Pb isotope signature levels. The source apportionment results revealed that in an industrial city with many steel and coking plants, the primary source of PM2.5 -bound Pb were motor vehicle emission (29.7%) and coal combustion (26.9%), rather than industrial emission (26.5%). Moreover, seasonal variations in PM2.5 of Pb sub-sources were observed: soil dust (21.7% and 18.4%) and diesel motor vehicles emission (16.4% and 15.6%) in summer and autumn; domestic coal combustion (17.1%) and coal-fired power plant emission (15.5%) in winter. The carcinogenic risk from motor vehicle emission in autumn was higher than that from industrial and coal sources in winter, and higher than that from motor vehicle sources in summer. This finding is a critical evidence of an anomalistic enrichment of PM2.5 -bound Pb in an industrial city. These results obtained through Pb isotopic composition and MixSIAR model also improved the accuracy of source apportionment of atmospheric PM2.5 -bound Pb, representing a high scientific significance and reference value for Pb pollution control in North China. Highlights: Pb isotopic analysis was used for source apportionment of PM2.5 -bound Pb. Pb isotope ratios of sources identified has significant specificity. Pb isotopic composition in PM2.5 is dispersed and its sources are complex. Motor vehicle exhaust was the main source of PM2.5 -bound Pb. The heating of domestic coal during winters was the major contributor.